2D visual codes: why are they not everywhere? - Oliveira, Sérgio (2008)
One key characteristic of ubiquitous computing is the disappearing boundary between physical and virtual elements, a mindset shift from interaction with the computer to the interaction with the environment. 2D visual codes are an important enabling technology for this increasing integration between physical spaces and virtual. However, despite the availability of a broad range of technologies for 2D visual codes, their common usage is still far from being a reality. In this work, we explore some of the factors that may influence the adoption of such interaction techniques. The study was based on the development of a prototype in which a set of applications was made available through interaction with visual codes. The prototype was deployed for three months in a public setting where users could try this technology for themselves. The results from the study suggest that visual codes are seen as a simple interaction model, but still some brief initial introduction may be needed. The study has also highlighted some functional limitations and strong technical constraints that proved to be very demanding when considered in the context of a real scenario and using people’s own devices. Although the curiosity factor plays very favourable to the visual codes, its generalized adoption will be difficult or, at least, will not happen as spontaneously as a simple demo may initially suggest.